Decreased plasma concentrations of brain-derived neurotrophic factor (BDNF) in patients with functional hypothalamic amenorrhea. (11th July 2013) - Podfigurna-Stopa, Agnieszka; Casarosa, Elena; Luisi, Michele; Czyzyk, Adam; Meczekalski, Blazej; Genazzani, Andrea Riccardo
Abstract: Introduction : Functional hypothalamic amenorrhea (FHA) is a non organic, secondary amenorrhea related to gonadotropin-releasing hormone pulsatile secretion impairment. Brain-derived neurotrophic factor (BDNF), a member of the neurotrophin family of survival-promoting molecules, plays an important role in the growth, development, maintenance and function of several neuronal systems. Aim of the study : The aim of the study was the evaluation of plasma BDNF concentrations in patients with the diagnosis of FHA. Material and methods . We studied 85 subjects diagnosed with FHA who were compared with 10 healthy, eumenorrheic controls with normal body mass index. Plasma BDNF and serum luteinizing hormone, follicle-stimulating hormone and estradiol (E2) concentrations were measured by immunoenzymatic method (enzyme-linked immunosorbent assay). Results : Significantly lower concentration of plasma BDNF was found in FHA patients (196.31 ± 35.26 pg/ml) in comparison to healthy controls (407.20 ± 25.71 pg/ml; p  < 0.0001). In the control group, there was a strong positive correlation between plasma BDNF and serum E2 concentrations ( r  = 0.92, p  = 0.0001) but in FHA group it was not found. Conclusions : Role of BDNF in FHA is not yet fully understood. There could be found studies concerning plasma BDNF concentrations in humans and animals in the literature. However, our study is one of the first projects which describes decreased plasma BDNF concentration in patients with diagnosed FHA. Therefore, further studies on BDNF in FHA should clarify the role of this peptide.